UNHCR and International Refugee Law : From Treaties to Innovation. - Lewis, Corinne (Routledge research in international law., 2012)
This book considers the United Nations High Commissioner for Refugees' contribution to international refugee law since the establishment of UNHCR by the United Nations General Assembly in 1951. The book explores the historical and statutory foundations that create an indelible link between UNHCR and international refugee law. This book charts the significant evolution that has occurred in the organisation's role throughout the last sixty years, looking at both the formal means by which UNHCR's mandate may be modified, and the techniques UNHCR has used to facilitate the changes in its role.